PENGARUH METODE THINK PAIR SHARE TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS IV SD NEGERI PELANG LOR 1 - Sigit Adi Wibowo; Nofita Lestariningsih; Aulia Fajar Khasanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Think Pair Share (TPS) method on the Indonesian language learning outcomes, specifically in narrative text material, of fourth-grade students at SD Negeri Pelang Lor 1. The research employed a quantitative method with a quasi-experimental design using a Nonequivalent Control Group Design. The population consisted of 54 students, divided into 26 students at SDN Pelang Lor 1 as the experimental group and 28 students at SDN Soco 2 as the control group, selected via total sampling (sampling jenuh). Data were collected using a 20-item multiple-choice test instrument that had met the requirements for validity, reliability, difficulty index, and discriminating power. Data analysis was conducted using the Kolmogorov-Smirnov normality test, Levene's homogeneity test, and the Independent Sample t-Test via SPSS Statistics 24. The results showed that the average posttest learning outcome of the experimental group was 79.81, which was higher than the control group's average of 63.57. The Independent Sample t-Test obtained a significance value of 0.000 < 0.05, leading to the rejection of H0 and acceptance of H1. It can be concluded that the Think Pair Share method has a significant effect on improving the Indonesian language learning outcomes in narrative text material of fourth-grade students at SD Negeri Pelang Lor 1.